Detection method of packaging substrate, electronic equipment and computer readable storage medium

By using ion beam grinding and electron beam backscattering diffraction technology at the bottom of the blind hole of the package substrate, the grain boundaries and microstructure of different copper layers at the bottom of the blind hole were successfully characterized, solving this problem that the existing technology is difficult to effectively characterize, and achieving The damage-free structure characterization and performance analysis of blind holes of package substrates were performed.

CN119413823AActive Publication Date: 2025-02-11GREATECH SUBSTRATES CO LTD

Patent Information

Application Number
CN202411398306.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-11
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The prior art is difficult to effectively characterize the grain boundaries and microstructures of different copper layers at the bottom of the blind hole of the package substrate, resulting in the failure mode of the blind hole of the package substrate being fully understood and improved.

Method used

Using a detection method, including obtaining a sample to be tested with a blind hole structure from the package substrate, and grinding the grain boundary between the first metal layer and the second metal layer with an ion beam along the cross section of the sample to be tested , the groove is formed, and then the groove is backscattered and diffraction using electron beam to obtain grain diffraction images and cross-sectional morphology images, and combined with analysis to characterize the microstructure information at the bottom of the blind hole.

Benefits of technology

This method can effectively characterize the grain boundaries and microstructures of different copper layers at the bottom of the blind hole of the package substrate, and is used to characterize and perform performance analysis of the damage-free structure at the bottom of the blind hole of the package substrate, thereby improving the reliability of the blind hole.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119413823A_ABST
    Figure CN119413823A_ABST
Patent Text Reader

Abstract

The invention discloses a detection method of a packaging substrate, electronic equipment and a computer readable storage medium. The method comprises the following steps: obtaining a to-be-tested sample with a blind hole structure from a packaging substrate; the blind hole bottom of the blind hole structure at least comprises a first metal layer and a second metal layer; grinding the grain boundary between the first metal layer and the second metal layer by using an ion beam along the cross section vertical to the sample to be tested to form a groove on the cross section of the sample to be tested; carrying out back scattering diffraction on the groove by using an electron beam to obtain a grain diffraction image corresponding to the bottom of the blind hole, and obtaining a cross section morphology image representing the grain boundary; the grain diffraction image and the cross section morphology image are combined for analysis, microstructure information representing the bottom of the blind hole is obtained, grain boundaries and microstructures of different copper layers at the bottom of the blind hole of the packaging substrate can be effectively represented, and the method is further used for non-damage structure representation and performance analysis of the bottom of the blind hole of the packaging substrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of packaging substrates, and in particular to a packaging substrate detection method, electronic equipment, and computer-readable storage medium. Background Art

[0002] The blind hole stacking structure of the package substrate plays a vital role in achieving the electrical connection between the surface circuit and the inner layer circuit. Among them, the microstructure at the bottom of the blind hole is usually composed of three layers, namely the inner electroplated copper layer, the chemically deposited copper layer and the outer hole-filling electroplated copper layer. Due to the different deposition principles of the electroplated copper layer and the chemically deposited copper layer, there are differences in the crystallization state of the copper grains. The grain differences between these layers form a complex microstructure. The microstructure at the bottom of the blind hole has a great impact on the reliability of the package substrate, especially in extreme environments such as cold and hot shocks. The mismatch at the grain boundary of the grain structure can easily lead to the generation of microcracks, thereby causing interlayer interconnection failure.

[0003] At present, on the one hand, it is difficult to clearly image the bottom of the blind hole using a scanning electron microscope (SEM), especially to clearly distinguish the grain boundaries and structures of different copper layers. On the other hand, characterizing the bottom of the blind hole by a transmission electron microscope (TEM) is cumbersome to prepare and the photography cost is high.

[0004] Therefore, there is a lack of effective characterization and analysis methods for the microstructure characterization methods at the grain boundaries of different processes at the bottom of the blind vias and their relationship with performance, resulting in the inability to fully understand and improve the failure mode of the blind vias in the packaging substrate. Summary of the invention

[0005] The main technical problem solved by the present application is to provide a packaging substrate detection method, electronic device and computer-readable storage medium, which can effectively characterize the grain boundaries and microstructures of different copper layers at the bottom of the blind hole of the packaging substrate, and then be used for damage-free structural characterization and performance analysis of the bottom of the blind hole of the packaging substrate.

[0006] In order to solve the above technical problems, a technical solution adopted in this application is: the detection method comprises:

[0007] Obtaining a sample to be tested having a blind hole structure from a packaging substrate; the bottom of the blind hole of the blind hole structure at least includes a first metal layer and a second metal layer;

[0008] Along a cross section perpendicular to the sample to be tested, grinding the grain boundary between the first metal layer and the second metal layer by using an ion beam to form a groove on the cross section of the sample to be tested;

[0009] Performing backscatter diffraction on the groove using an electron beam to obtain a grain diffraction image corresponding to the bottom of the blind hole, and obtaining a cross-sectional morphology image representing the grain boundary;

[0010] The grain diffraction image and the cross-sectional morphology image are analyzed in combination to obtain microstructure information characterizing the bottom of the blind hole.

[0011] Optionally, grinding the grain boundary between the first metal layer and the second metal layer by using an ion beam along a cross section perpendicular to the sample to be tested to form a groove on the cross section of the sample to be tested includes:

[0012] Obtaining a fixed angle between the irradiation direction of the electron beam and the tilt direction of the cross section of the sample to be tested;

[0013] Based on the fixed angle, the relative angles of the side lines on both sides of the groove are determined, and the grain boundary is ground using the ion beam based on preset ion grinding parameters to form a groove on the cross section of the sample to be tested.

[0014] Optionally, the method of determining the relative angles of the side lines of the groove on both sides based on the fixed angle, and using the ion beam to grind the grain boundary based on preset ion milling parameters to form the groove on the cross section of the sample to be tested includes:

[0015] Determine the relative angle of the side lines of the groove on both sides in combination with the preset vertical angle and the fixed angle, so that 1 / 2 of the relative angle is equal to or greater than the incident angle of the electron beam relative to the groove;

[0016] Along the grain boundary, the cross section of the sample to be tested is controlled to rotate horizontally, so as to use the ion beam to grind the grain boundary based on the ion milling parameters to form a groove on the cross section of the sample to be tested.

[0017] Optionally, the ion milling parameters include at least one of a working voltage of 3 kV to 5 kV, a milling temperature less than or equal to 100° C., an ion beam angle of 80° to 85°, and a milling time of 20 to 100 minutes.

[0018] Optionally, obtaining a sample to be tested having a blind hole structure from a packaging substrate includes:

[0019] Obtaining an initial sample having the blind hole structure from the packaging substrate;

[0020] According to the diffraction conditions of the electron beam, the initial sample is ground and surface treated to obtain the sample to be tested.

[0021] Optionally, grinding and surface treating the initial sample according to the diffraction condition of the electron beam to obtain the sample to be tested comprises:

[0022] Grinding the burr edge of the initial sample to form a first sample, so that the cross section of the first sample is parallel to the stage;

[0023] placing the cross section of the first sample horizontally in a container, and filling the container with an organic material to obtain a cured second sample;

[0024] Grinding the second sample to a size according to a working distance between the stage and the electron beam to form a third sample;

[0025] According to the back diffraction thickness of the electron beam, the surface scratches of the third sample are ground, and the ground third sample is polished to form the sample to be tested.

[0026] Optionally, grinding the surface scratches of the third sample and polishing the ground third sample to form the sample to be tested includes:

[0027] Using sandpaper of various grits to grind the surface scratches of the third sample in descending order;

[0028] The ground third sample is polished until no scratches exist on the blind hole structure under a preset microscope magnification, thereby forming the sample to be tested.

[0029] Optionally, the combining the grain diffraction image and the cross-sectional morphology image for analysis to obtain microstructure information characterizing the bottom of the blind hole includes:

[0030] Acquiring information on grain size and grain growth status from the grain diffraction image;

[0031] The cross-sectional morphology image characterizing the grain boundary, the grain size and the grain growth condition information are combined to obtain microstructure information characterizing the bottom of the blind hole.

[0032] In order to solve the above technical problems, another technical solution adopted by the present application is: an electronic device, the electronic device comprising:

[0033] A memory for storing executable program codes;

[0034] A processor is used to call and run the executable program code from the memory, so that the electronic device executes the packaging substrate detection method as described in any one of the above.

[0035] To solve the above technical problems, another technical solution adopted in the present application is: a computer-readable storage medium, wherein the computer-readable storage medium stores a computer program, and when the computer program is executed by a processor, the packaging substrate detection method as described in any one of the above items is implemented.

[0036] Different from the prior art, an embodiment of the present application provides a method for detecting a packaging substrate, the method comprising: obtaining a sample to be tested having a blind hole structure from a packaging substrate; the bottom of the blind hole of the blind hole structure comprises at least a first metal layer and a second metal layer; along a cross section perpendicular to the sample to be tested, grinding the grain boundary between the first metal layer and the second metal layer using an ion beam to form a groove on the cross section of the sample to be tested; performing backscatter diffraction on the groove using an electron beam to obtain a grain diffraction image corresponding to the bottom of the blind hole, and obtaining a cross-sectional morphology image characterizing the grain boundary; analyzing the grain diffraction image and the cross-sectional morphology image in combination to obtain microstructural information characterizing the bottom of the blind hole, which can effectively characterize the grain boundaries and microstructures of different copper layers at the bottom of the blind hole of the packaging substrate, and further be used for non-destructive structural characterization and performance analysis of the bottom of the blind hole of the packaging substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is an exemplary schematic diagram of a blind hole stacking hole structure of the detection method of the packaging substrate of the present application;

[0038] Figure 2 It is a flow chart of the first embodiment of the detection method of the packaging substrate of the present application;

[0039] Figure 3 It is a flow chart of a second embodiment of a method for detecting a package substrate of the present application;

[0040] Figure 4a This is an exemplary schematic diagram of sampling of a sample to be tested in the method for detecting a package substrate of the present application;

[0041] Figure 4b It is an exemplary schematic diagram of a blind hole pre-grinding process of the packaging substrate detection method of the present application;

[0042] Figure 4c It is an exemplary schematic diagram of the preparation of a blind hole microstructure sample in the detection method of the package substrate of the present application;

[0043] Figure 4d It is an exemplary schematic diagram of a sample size grinding process of a method for detecting a package substrate of the present application;

[0044] Figure 4e It is an exemplary schematic diagram of sample fine grinding of the detection method of the package substrate of the present application;

[0045] Figure 4f It is an exemplary schematic diagram of sample surface reprocessing in the detection method of the package substrate of the present application;

[0046] Figure 4g is an exemplary schematic diagram of the EBSD characterization of the detection method of the package substrate of the present application;

[0047] Figure 5a is a first exemplary schematic diagram of a cross-sectional topography image of a method for detecting a package substrate of the present application;

[0048] Figure 5b is a second exemplary schematic diagram of a cross-sectional topography image of a method for detecting a package substrate of the present application;

[0049] Figure 5c is a third exemplary schematic diagram of a cross-sectional topography image of a method for detecting a package substrate of the present application;

[0050] Figure 5d is a fourth exemplary schematic diagram of a cross-sectional topography image of a method for detecting a package substrate of the present application;

[0051] Figure 5e is a fifth exemplary schematic diagram of a cross-sectional topography image of a method for detecting a package substrate of the present application;

[0052] Figure 6a is a first exemplary schematic diagram of a grain diffraction image of a method for detecting a package substrate of the present application;

[0053] Figure 6b is a second exemplary schematic diagram of a grain diffraction image of the detection method of the packaging substrate of the present application;

[0054] Figure 6c is a third exemplary schematic diagram of a grain diffraction image of the method for detecting a packaging substrate of the present application;

[0055] Figure 6d is a fourth exemplary schematic diagram of a grain diffraction image of a method for detecting a package substrate of the present application;

[0056] Figure 6e is a fifth exemplary schematic diagram of a grain diffraction image of a method for detecting a package substrate of the present application;

[0057] Figure 7 It is a schematic diagram of the reverse polarity of the copper grain at the bottom of the blind hole in the detection method of the packaging substrate of the present application;

[0058] Figure 8a It is a statistical diagram of the size of the electroplated copper grains in the hole of the detection method of the package substrate of the present application;

[0059] Figure 8bIt is a statistical diagram of the size of the electroplated copper grains at the bottom of the hole in the detection method of the package substrate of the present application;

[0060] Fig. 9 It is an exemplary structural block diagram of an electronic device of the method for detecting a package substrate of the present application;

[0061] Fig.10 It is an exemplary structural block diagram of a computer-readable storage medium of the method for detecting a package substrate of the present application.

[0062] Reference numerals: outer hole-filling electroplated copper layer 1, chemically deposited copper layer 2, inner electroplated copper layer 3. DETAILED DESCRIPTION

[0063] The present application is described in detail below with reference to the accompanying drawings and implementation methods.

[0064] This embodiment takes into account that the blind hole stacking structure is used to connect the surface circuit and the inner circuit to achieve normal electrical conductivity of the circuit. The microstructure at the bottom of the blind hole is composed of three parts. In an exemplary embodiment, the schematic diagram of the blind hole stacking structure can be referred to Figure 1 The bottom of the blind hole is composed of an outer hole-filling electroplated copper layer 1, a chemically deposited copper layer 2, and an inner electroplated copper layer 3.

[0065] Overall, the bottom of the blind hole contains only one metallic copper element. However, due to the different preparation principles of the electroplated copper layer and the chemically deposited copper layer, grain boundaries appear between the inner electroplated copper layer and the chemically deposited copper layer, or between the outer hole-filling electroplated copper layer and the chemically deposited copper layer. The grain boundaries indicate differences in the crystallization state of the copper grains. Specifically, the electroplated copper layer is deposited on a single copper metal by an electrodeposition method. The copper grains of the inner electroplated copper layer tend to grow into columnar crystals along the filling direction, and the grain size is relatively large. The copper grains of the outer hole-filling electroplated copper layer tend to grow randomly without strong texture. The chemically deposited copper layer deposits a thin layer of copper through an oxidation-reduction reaction. The thickness of the copper layer is about several hundred nanometers, the grain size is relatively small, and there are a large number of grain boundaries.

[0066] However, it is difficult to clearly characterize the microstructure at the bottom of the blind hole using the current scanning electron microscope (SEM) imaging. In addition, since there is only one metal element at the bottom of the blind hole, it is difficult to clearly identify the specific location of the grain boundary after the blind hole copper filling process is completed. It is difficult to distinguish the microstructure of different electroplated copper layers, and thus it is impossible to analyze the microstructure at the bottom of the blind hole, as well as the relationship between structure and performance.

[0067] Therefore, this embodiment provides an electron backscatter diffraction (EBSD) sample and a preparation method for characterizing the microstructure at the grain boundary of a blind hole.

[0068] See also Figure 2 , Figure 2 FIG. 1 is a flow chart of the first embodiment of the method for detecting a package substrate of the present application. It should be noted that if there are substantially the same results, the method of the present application is not limited to Figure 2 The process sequence shown is limited. Figure 2 As shown, the detection method comprises:

[0069] Step S210, obtaining a sample to be tested having a blind hole structure from a packaging substrate; the bottom of the blind hole of the blind hole structure at least includes a first metal layer and a second metal layer;

[0070] Among them, the packaging substrate can be the core structure used to carry and interconnect electronic components in electronic devices, used to support chips and conduct electricity. The packaging substrate is mainly composed of an insulating substrate, a copper layer, an organic build-up film, and a solder resist ink. The function of the blind hole stacking structure of the packaging substrate is to connect each layer of the circuit to achieve normal electrical conductivity of the circuit. The blind hole structure can also be a blind hole stacking structure. The sample to be tested can be a sample that meets the electron backscatter diffraction conditions and the ion beam grinding conditions.

[0071] In an exemplary embodiment, the first metal layer and the second metal layer may be an inner electroplated copper layer and a chemically deposited copper layer. In another exemplary embodiment, the first metal layer and the second metal layer may be an outer electroplated copper layer and a chemically deposited copper layer.

[0072] Step S220, grinding the grain boundary between the first metal layer and the second metal layer using an ion beam along a cross section perpendicular to the sample to be tested, to form a groove on the cross section of the sample to be tested;

[0073] The cross section may be the internal structure surface exposed by the sample to be tested after cutting. Ion beam cross section polishing (CP) may be to use ion beam polishing technology to take out the cross section of the sample to be tested along the cross section perpendicular to the object to be tested, which can avoid the influence of stress generated by the polishing process to prepare the groove on the cross section at the bottom of the blind hole. The groove can be used to expose the internal structure of the bottom of the blind hole, which is convenient for the subsequent analysis of the grain boundaries and grain orientations of different metal layers.

[0074] Specifically, in order to allow the electron beam to enter the microstructure at the bottom of the blind hole at a suitable angle, the ion beam can be used to grind and groove the bottom of the blind hole to expose the internal structure at the bottom of the blind hole and make it easier to analyze. At the same time, the groove angle can also take into account the irradiation conditions of the electron beam to ensure that the electron beam can irradiate the grain boundary at a suitable angle in the electron backscatter diffraction analysis.

[0075] Step S230, performing backscatter diffraction on the groove using an electron beam to obtain a grain diffraction image corresponding to the bottom of the blind hole, and obtaining a cross-sectional morphology image representing the grain boundary;

[0076] Specifically, the electron beam can be a high-energy electron stream. When the electron beam irradiates the groove of the sample to be tested, backscattered electrons or other signals can be generated to obtain a grain diffraction image. The grain diffraction image can characterize the growth condition and size of the grains, and can be used to analyze the stress concentration points at the grain boundaries and possible microcracks. The cross-sectional morphology image can be an image obtained by a tool such as an electron microscope, which is used to show the specific location of the grain boundary.

[0077] Step S240, analyzing the grain diffraction image and the cross-sectional morphology image to obtain microstructure information characterizing the bottom of the blind hole.

[0078] Specifically, microstructure information refers to the microstructure of different metal layers at the grain scale, including grain size, orientation, grain boundary distribution, and the presence of microcrack defects. By obtaining microstructure information, we can deeply understand the quality of the electroplating layer at the bottom of the blind hole and the bonding at the grain boundary, analyze the potential failure area of ​​the blind hole, and thus improve the design and manufacturing process of the packaging substrate.

[0079] In an exemplary embodiment, first, a sample to be tested having a blind hole bottom structure is prepared, and the blind hole structure of the sample to be tested can be clearly seen under a metallographic microscope; the area where the blind hole structure is located is treated with an argon ion beam to produce a groove with a larger angle at the bottom of the blind hole. The angle of the groove satisfies the condition that the electron beam can obtain information at the grain boundary. For example, if the angle between the EBSD electron gun and the sample to be tested is θ and the angle of the groove at the bottom of the blind hole is α, the condition for the electron beam to obtain information at the grain boundary is θ≥90°-1 / 2α; at the same time, the ion milling parameters of the ion beam are controlled to achieve a metallographic microscope that can clearly characterize the microstructure at the bottom of the blind hole at a magnification of 50×, so that the grooves generated on the surface of the sample to be tested will not affect the EBSD image quality. Then, carbon is sprayed on the sample surface to increase conductivity and EBSD is taken to characterize the microstructure at the bottom of the blind hole. In this way, samples that characterize the blind hole structure can be effectively prepared and the specific microstructure at the bottom of the blind hole can be analyzed, which can be extended to the preparation of samples for characterizing the microstructure at the grain boundary of various materials for different processes. It can not only meet the requirements of EBSD pre-treatment conditions, but also clearly confirm the specific location of the grain boundary at the bottom of the blind hole through the SEM image displayed by BESD. The obtained EBSD image is of high quality and can be used to study the structure and properties of blind holes and the microstructure at the grain boundaries of different materials.

[0080] This embodiment uses an ion beam to groove the bottom of the blind hole along a cross section perpendicular to the sample to be tested to form a groove, and then uses an electron beam to perform backscatter diffraction on the groove to obtain a grain diffraction image and a cross-sectional morphology image and combine the analysis to effectively characterize the grain boundaries and microstructures of different copper layers at the bottom of the blind hole of the packaging substrate, and then be used for non-destructive structural characterization and performance analysis of the bottom of the blind hole of the packaging substrate.

[0081] This embodiment takes into account that the blind hole copper filling process of interlayer interconnection is a key technology for realizing high-density interconnection manufacturing, and the structure and performance of electroplated copper are key factors affecting the high reliability of interlayer interconnection. There is a large difference in the microstructure of copper grains between the chemically deposited copper layer and the electroplated copper layer, which leads to a high lattice mismatch at the crystal grain boundary. From the perspective of phase boundary energy, the energy at the total grain boundary is higher. In the analysis of the results of the hot and cold shock reliability test of the packaging substrate, if the local thermal stress exceeds the threshold during the hot and cold shock process, microcracks are easily generated between the chemically deposited copper layer and the inner electroplated copper layer, and / or between the chemically deposited copper layer and the outer hole-filling electroplated copper layer, resulting in failure.

[0082] However, on the one hand, scanning electron microscope imaging cannot currently clearly characterize the microstructure at the bottom of the blind hole. In addition, since there is only one metal element at the bottom of the blind hole, it is difficult to clarify the specific location of the grain boundary after the blind hole copper filling process is completed. It is difficult to distinguish the microstructure of different electroplated copper layers, and thus it is impossible to analyze the microstructure at the bottom of the blind hole, and it is impossible to establish the relationship between structure and performance. On the other hand, characterizing the bottom of the blind hole by transmission electron microscopy is cumbersome to prepare samples and the cost of shooting is high.

[0083] Therefore, this embodiment proposes a method for detecting the failure mechanism of microcracks and the microstructure and performance of the bottom of the blind hole, which effectively realizes the specific analysis of the microstructure of the bottom of the blind hole and the failure of the blind hole, and then regulates the copper grain microstructure of the packaging substrate and the reliability of the blind hole. Figure 3 , Figure 3 1 is a flow chart of a second embodiment of a method for detecting a package substrate of the present application. In this embodiment, the method comprises the following steps:

[0084] Step S310, obtaining an initial sample having the blind hole structure from the packaging substrate;

[0085] Specifically, the sampling can be performed on the area where the blind hole structure of the package substrate is concentrated, which has been processed through normal processes. Figure 4a , the size of the sample to be tested can be controlled to not exceed 30mm×30mm×30mm.

[0086] Step S320: grinding and surface treating the initial sample according to the diffraction condition of the electron beam to obtain the sample to be tested.

[0087] Specifically, in order to obtain a clear grain diffraction image, the sample to be tested can be controlled to meet the preset electron beam diffraction conditions. If the surface of the sample to be tested is too rough or there are other interference factors, it is easy to affect the accuracy of diffraction. Therefore, when grinding and surface treating the initial sample, ensure that the final sample to be tested reaches a surface quality and state suitable for diffraction.

[0088] In an exemplary embodiment, the electron beam diffraction conditions may include an acceleration voltage, a beam intensity, an incident angle, and the like of the electron beam.

[0089] Further, step S320 includes:

[0090] Grinding the burr edge of the initial sample to form a first sample, so that the cross section of the first sample is parallel to the stage;

[0091] Specifically, in order to ensure that the cross section containing the blind hole structure can be parallel to the sample stage carrying the sample during the sample preparation process, signal loss during the EBSD diffraction pattern acquisition process can be avoided. In an exemplary embodiment, please refer to Figure 4b The edge of the initial sample can be polished so that there are no obvious burrs on the surface of the first sample after polishing, thereby making the cross section (observation surface) of the sample parallel to the sample stage.

[0092] placing the cross section of the first sample horizontally in a container, and filling the container with an organic material to obtain a cured second sample;

[0093] Specifically, the organic material is used to ensure that there are no obvious bubbles after the second sample is prepared, so as not to affect the EBSD characterization observation. The organic material can be an organic material with good fluidity, including but not limited to epoxy resin, silicone and polyurethane potting glue.

[0094] In an exemplary embodiment, see Figure 4c For the first sample after pre-grinding, the cross section of the first sample containing the blind hole microstructure is placed horizontally upward in a container, and the container is filled with an organic material to be cured with good fluidity and left to stand for at least 5 minutes to ensure that the organic material is completely cured to form a cured second sample. It is ensured that no obvious bubbles are generated after the sample preparation is completed to avoid affecting the subsequent characterization observation.

[0095] Grinding the second sample to a size according to a working distance between the stage and the electron beam to form a third sample;

[0096] Specifically, since the distance between the stage and the electron gun probe is limited during EBSD shooting, a larger sample may touch the probe and cause damage to the instrument. Therefore, the second sample can be ground to the size to form a third sample.

[0097] In an exemplary embodiment, see Figure 4d The second sample is ground by a grinder to form a third sample, and the size of the third sample is controlled within 10 mm×10 mm×10 mm.

[0098] According to the back diffraction thickness of the electron beam, the surface scratches of the third sample are ground, and the ground third sample is polished to form the sample to be tested.

[0099] Specifically, sandpaper with various grit sizes can be used to grind the surface scratches of the third sample in order from large to small; the ground third sample is polished until there are no scratches on the blind hole structure under a preset microscope magnification, thereby forming the sample to be tested.

[0100] In an exemplary embodiment, considering that the EBSD data is derived from the area within 100 nm of the sample surface, obvious scratches cannot be removed in subsequent steps, and the ion beam polishing only bombards the nanoscale surface. Figure 4e The third sample was ground with sandpaper of different grits, the sizes of which were sandpaper of 10 μm or more, sandpaper of 3 μm to 10 μm, and sandpaper of 3 μm or less. After grinding, the sample was polished with a polishing machine, and observed with a metallographic microscope during the polishing process until a clear blind hole structure appeared at 50× magnification and no obvious scratches appeared in the field of view, and the blind hole structure was clearly visible and the aperture size was within the median range of the processing specifications.

[0101] Step S330, obtaining a fixed angle between the irradiation direction of the electron beam and the tilt direction of the cross section of the sample to be tested;

[0102] Specifically, the fixed angle refers to the angle between the electron beam irradiation direction and the cross section of the sample to be measured. In microscopic analysis, this angle is usually fixed to ensure that the electron beam is incident on the sample surface in a specific way.

[0103] Step S340, based on the fixed angle, determine the relative angles of the side lines of the groove, and use the ion beam to grind the grain boundary based on preset ion milling parameters to form a groove on the cross section of the sample to be tested.

[0104] Specifically, the shape of the groove and the relative angles of the two side edges need to be precisely controlled to ensure that key areas such as grain boundaries are exposed to the maximum extent, so that the microstructure at the bottom of the blind hole or the grain boundary can be more clearly observed during electron beam analysis.

[0105] Further, the area where the blind hole microstructure is observed under the metallographic microscope is subjected to argon ion beam polishing, and the polishing mode of the ion beam is controlled to be a mode suitable for bombarding copper metal grains, and the ion milling parameters of the argon ion beam include at least one of a working voltage of 3kV to 5kV, a milling temperature less than or equal to 100°C, an ion beam angle of 80° to 85°, and a milling time of 20 to 100 minutes. Further, the preferred milling time is 50 to 100 minutes, and the grooves under this milling time can make the imaging quality of the grain diffraction image higher.

[0106] During the process of ion beam milling the grain boundary at the bottom of the blind hole, the sample to be tested can be kept rotating horizontally to complete uniform etching of the groove.

[0107] Further, step S340 includes:

[0108] In combination with the preset vertical angle and the fixed angle, the relative angle of the two side edges of the groove is determined so that 1 / 2 of the relative angle is equal to or greater than the incident angle of the electron beam relative to the groove; along the grain boundary, the cross section of the sample to be tested is controlled to rotate horizontally so as to use the ion beam to grind the grain boundary based on the ion milling parameters to form a groove on the cross section of the sample to be tested.

[0109] Specifically, half of the relative angle of the two sides of the groove should be equal to or greater than the electron beam incident angle, which can ensure that the electron beam can effectively irradiate the inside of the groove, especially the key areas such as the grain boundary. It can ensure that the electron beam can fully penetrate into the sample, so as to obtain accurate diffraction data or morphological information. Horizontal rotation refers to the rotation of the sample to be tested on the horizontal plane, so that the ion beam can be evenly ground along the grain boundary, so that a clearly visible groove line appears in the cross section.

[0110] In an exemplary embodiment, see Figure 4f and Figure 4g , assuming that the electron beam emitted by the electron gun in the EBSD equipment is fixed at an angle of 20° to the sample, the angle of the groove at the bottom of the blind hole must be controlled to be greater than or equal to 140°, otherwise it will seriously affect the signal of the later EBSD characterization and cause signal loss. It is required that a clearly visible groove line appears on the surface of the sample. After ion beam milling, the milling area is immediately sealed and marked.

[0111] Step S350, performing backscatter diffraction on the groove using an electron beam to obtain a grain diffraction image corresponding to the bottom of the blind hole, and obtaining a cross-sectional morphology image representing the grain boundary;

[0112] In an exemplary embodiment, after argon ion beam milling, a signal enhancement process is performed on the sample to be tested for which the milling effect has been confirmed. By sputtering a conductive coating on the surface of the sample to be tested, a good conductive coating can be provided for EBSD characterization, thereby obtaining a good diffraction pattern. The conductive coating includes but is not limited to a carbon layer, a gold layer, etc.

[0113] Step S360, obtaining information on grain size and grain growth status from the grain diffraction image;

[0114] In an exemplary embodiment, see Figure 4g , the microscopic morphology of the surface of the sample to be tested is detected by ultra-depth three-dimensional microscope or scanning electron microscope. Specifically, the sample is fixed on an inclined stage, and the microstructure of the bottom of the blind hole is characterized by EBSD to obtain a grain diffraction image (EBSD image). At the same time, the information of the grain boundary at the bottom of the blind hole can be confirmed by a scanning electron microscope and a cross-sectional morphology image (SEM image) at the same time. Confirming the specific position of the grain boundary helps to analyze the microscopic information such as the size and orientation of the copper grains at the grain boundary.

[0115] Step S370, combining the cross-sectional morphology image characterizing the grain boundary, the grain size and the grain growth condition information, to obtain microstructure information characterizing the bottom of the blind hole.

[0116] In an exemplary embodiment, ion milling can be a method of sputtering a material surface using an argon ion beam, which does not cause mechanical damage to the sample and can obtain a high-quality sample with a smooth surface. This embodiment is to prepare an EBSD sample, and the sample can be processed by ion milling to obtain a flat surface. The following content is used to compare different ion milling conditions to determine the optimal ion milling conditions, thereby obtaining a high-quality EBSD image.

[0117] When the ion beam incident angle is ≥80°, the ion beam irradiation angle is almost parallel to the sample processing surface, which can reduce the unevenness caused by the crystal orientation and component etching rate difference, and form a smooth processing surface. In order to compare the effect of grinding time on sample flatness, two-step stacking holes in the same area are set as the grinding object of the ion beam, and experimental groups with different grinding times of the ion beam are set. Please refer to Figure 5a to Figure 5e , Figure 5a to Figure 5e The SEM images of the grooves on the bottom surface of the blind hole in each experimental group are the grooves at grinding times of 20 minutes, 35 minutes, 50 minutes, 65 minutes, and 80 minutes, respectively. Figure 5a The groove angle a is obtained when the grinding time is 20 minutes; Figure 5b The b-angle groove at a grinding time of 35 minutes; Figure 5c The c-angle groove under the grinding time of 50 minutes; Figure 5d The d angle groove at a grinding time of 65 minutes; Figure 5e The groove with an angle of e when the grinding time is 80 minutes. It can be seen that the angles of a, b, c, d, and e gradually increase, and the angles of d and e are greater than 140°.

[0118] in, Figure 5a It shows that when the grinding time is 20 minutes, only the middle area of ​​the bottom of the blind hole has grooves, the grain boundary is not clear enough, there are many uneven areas on the surface, and there are many unresolved areas at the angle a of the groove at the bottom of the blind hole. As the grinding time increases, the etching degree of the groove at the grain boundary at the bottom of the blind hole gradually increases. Figure 5b It is shown that when the grinding time is 35 minutes, there are still convex spots on the sample surface, which causes the sample surface to be locally rough, and the angle of the groove at the bottom of the blind hole is b. Figure 5c It shows that when the grinding time is 50 minutes, the quality of the EBSD image is improved, but unresolved areas still appear at the grain boundaries in the EBSD image. Figure 5d It shows that when the grinding time is 65 minutes, the angle of the groove area at the bottom of the blind hole is d (d ≥ 140°), the grain boundary is relatively clear, and there are only point-like unresolved areas in the EBSD image. Figure 5e It shows that when the grinding time is 80 minutes, the angle of the groove at the bottom of the blind hole is e. From the microscopic morphology, the surface is relatively smooth, the grain boundary is clear, and the EBSD image quality is high. It can be seen that Figure 5a to Figure 5e The formation of the groove is mainly due to the different etching rates, which can make the position of the groove correspond to the grain boundary at the bottom of the blind hole. There are differences in the microstructure of the copper grains deposited by the chemically deposited copper layer and the inner electroplated copper layer. The copper grains obtained by the chemically deposited copper layer are smaller, the number of grain boundaries is larger, and the energy is higher. They are easily etched during the ion beam bombardment process to produce grooves.

[0119] After processing the experimental groups under the above grinding time with EBSD post-processing software, the microstructure EBSD images of the copper grains at the bottom of the blind hole under different grinding times were obtained, as shown in Figure 2. Figure 6a to Figure 6e Shown. Figure 6a It shows that there are a lot of white node areas in the upper left corner. The white nodes are unresolved areas, and the resolution of this part is low. Figure 6a Corresponds to Figure 5a The unresolved area is uneven, which affects the scattering ability of the incident electrons. Figure 6eThe absence of a large number of continuous unresolved white spots indicates that the EBSD image quality is high. Therefore, it can be seen that the ion beam milling time is 50 minutes to 100 minutes, and the quality of the generated EBSD image is high.

[0120] Furthermore, the microstructure information of the copper grains at the bottom of the blind hole is characterized, mainly focusing on the grain size and grain growth, such as Figure 7 As shown. From the grain morphology analysis, the electroplated copper grains in the hole grow randomly without strong texture. The electroplated copper grains at the bottom of the hole as the base copper mainly grow along the vertical direction, and the crystal plane orientation tends to the 001 crystal plane. From the grain size analysis, Figure 8a The average grain size of the electroplated copper in the hole is about 0.69 μm. Figure 8b The electroplated copper grain size at the bottom of the hole is shown to be small.

[0121] In this embodiment, by preliminarily grinding the sample with the bottom structure of the blind hole, a blind hole structure clearly visible under a microscope is obtained, and the specific observation position is determined; the blind hole structure to be observed is processed by using argon ion beam grinding technology, and attention is paid to controlling the angle of the groove at the bottom of the blind hole; the microstructure of the bottom of the blind hole is characterized by an EBSD device. As a result, the bottom section of the blind hole can not only save the tedious steps of confirming the information at the grain boundary at the bottom of the blind hole, but also can simultaneously confirm the information at the grain boundary under the pre-treatment conditions required by EBSD, and can also be used to study the microstructure of the copper grains at the bottom of the blind hole, including information such as grain size and grain orientation. This method is fully applicable to the study of the blind hole structure of the packaging substrate, and is convenient, fast and simple to operate.

[0122] See also Fig. 9 , Fig. 9 is an exemplary structural block diagram of an electronic device for the detection method of the package substrate of the present application. Fig. 9 As shown, the electronic device 900 of the present application may include a processor 901 and a memory 902, wherein the processor 901 and the memory 902 communicate with each other via a bus. The memory 902 stores program instructions for detecting a package substrate, and when the program instructions are executed by the processor 901, the processor implements a package substrate detection method in the above embodiment.

[0123] See also Fig.10 , Fig.10 is an exemplary structural block diagram of a computer-readable storage medium of the packaging substrate detection method of the present application. Fig.10 As shown, the computer readable storage medium 1000 stores a computer program 1001. When the computer program 1001 is executed by a processor on a computer, the computer executes the above-mentioned related method steps to implement a packaging substrate detection method in the above-mentioned embodiment.

[0124] The above scheme obtains a sample to be tested having a blind hole structure from a packaging substrate; the bottom of the blind hole of the blind hole structure includes at least a first metal layer and a second metal layer; along a cross section perpendicular to the sample to be tested, the grain boundary between the first metal layer and the second metal layer is ground using an ion beam to form a groove on the cross section of the sample to be tested; the groove is backscattered diffracted using an electron beam to obtain a grain diffraction image corresponding to the bottom of the blind hole, and a cross-sectional morphology image characterizing the grain boundary is obtained; the grain diffraction image and the cross-sectional morphology image are combined for analysis to obtain microstructural information characterizing the bottom of the blind hole, which can effectively characterize the grain boundaries and microstructures of different copper layers at the bottom of the blind hole of the packaging substrate, and then be used for damage-free structural characterization and performance analysis of the bottom of the blind hole of the packaging substrate.

[0125] In the several embodiments provided in the present application, it should be understood that the disclosed methods, electronic devices and storage media can be implemented in other ways. For example, the device implementation described above is only schematic. For example, the division of the modules or units is only a logical function division. There may be other division methods in actual implementation, such as multiple units or components can be combined or integrated into another system, or some features can be ignored or not executed. Another point is that the mutual coupling or direct coupling or communication connection shown or discussed can be an indirect coupling or communication connection through some interfaces, devices or units, which can be electrical, mechanical or other forms.

[0126] The units described as separate components may or may not be physically separated, and the components shown as units may or may not be physical units, that is, they may be located in one place or distributed on multiple network units. Some or all of the units may be selected according to actual needs to achieve the purpose of the present embodiment.

[0127] In addition, each functional unit in each embodiment of the present application may be integrated into one processing unit, or each unit may exist physically separately, or two or more units may be integrated into one unit. The above-mentioned integrated unit may be implemented in the form of hardware or in the form of software functional units.

[0128] If the integrated unit is implemented in the form of a software functional unit and sold or used as an independent product, it can be stored in a computer-readable storage medium. Based on this understanding, the technical solution of the present application is essentially or the part that contributes to the prior art or all or part of the technical solution can be embodied in the form of a software product, and the computer software product is stored in a storage medium, including a number of instructions to enable a computer device (which can be a personal computer, a server, or a network device, etc.) or a processor (processor) to perform all or part of the steps of the detection method described in each embodiment of the present application. The aforementioned storage medium includes: various media that can store program codes, such as a USB flash drive, a mobile hard disk, a read-only memory (ROM, Read-Only Memory), a random access memory (RAM, Random Access Memory), a disk or an optical disk.

[0129] The above description is only an implementation method of the present application, and does not limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A method for detecting a packaging substrate, characterized in that: The detection method comprises: Obtaining a sample to be tested having a blind hole structure from a packaging substrate; the bottom of the blind hole of the blind hole structure at least includes a first metal layer and a second metal layer; Along a cross section perpendicular to the sample to be tested, grinding the grain boundary between the first metal layer and the second metal layer by using an ion beam to form a groove on the cross section of the sample to be tested; Performing backscatter diffraction on the groove using an electron beam to obtain a grain diffraction image corresponding to the bottom of the blind hole, and obtaining a cross-sectional morphology image representing the grain boundary; The grain diffraction image and the cross-sectional morphology image are analyzed in combination to obtain microstructure information characterizing the bottom of the blind hole.

2. The detection method according to claim 1, characterized in that: The method comprises grinding the grain boundary between the first metal layer and the second metal layer by using an ion beam along a cross section perpendicular to the sample to be tested to form a groove on the cross section of the sample to be tested, comprising: Obtaining a fixed angle between the irradiation direction of the electron beam and the tilt direction of the cross section of the sample to be tested; Based on the fixed angle, the relative angles of the side lines on both sides of the groove are determined, and the grain boundary is ground using the ion beam based on preset ion grinding parameters to form a groove on the cross section of the sample to be tested.

3. The detection method according to claim 2, characterized in that: The method of determining the relative angles of the side lines of the groove on both sides based on the fixed angle, and using the ion beam to grind the grain boundary based on preset ion milling parameters to form a groove on the cross section of the sample to be tested includes: Determine the relative angle of the side lines of the groove on both sides in combination with the preset vertical angle and the fixed angle, so that 1 / 2 of the relative angle is equal to or greater than the incident angle of the electron beam relative to the groove; Along the grain boundary, the cross section of the sample to be tested is controlled to rotate horizontally, so as to use the ion beam to grind the grain boundary based on the ion milling parameters to form a groove on the cross section of the sample to be tested.

4. The detection method according to claim 2, characterized in that: The ion milling parameters include at least one of a working voltage of 3 kV to 5 kV, a milling temperature less than or equal to 100° C., an ion beam angle of 80° to 85°, and a milling time of 20 to 100 minutes.

5. The detection method according to claim 1, characterized in that: The method of obtaining a sample to be tested having a blind hole structure from a packaging substrate comprises: Obtaining an initial sample having the blind hole structure from the packaging substrate; According to the diffraction conditions of the electron beam, the initial sample is ground and surface treated to obtain the sample to be tested.

6. The detection method according to claim 5, characterized in that: The method of grinding and surface treating the initial sample according to the diffraction conditions of the electron beam to obtain the sample to be tested comprises: Grinding the burr edge of the initial sample to form a first sample, so that the cross section of the first sample is parallel to the stage; placing the cross section of the first sample horizontally in a container, and filling the container with an organic material to obtain a cured second sample; Grinding the second sample to a size according to a working distance between the stage and the electron beam to form a third sample; According to the back diffraction thickness of the electron beam, the surface scratches of the third sample are ground, and the ground third sample is polished to form the sample to be tested.

7. The detection method according to claim 6, characterized in that: The step of grinding the surface scratches of the third sample and polishing the ground third sample to form the sample to be tested comprises: Using sandpaper of various grits to grind the surface scratches of the third sample in descending order; The ground third sample is polished until no scratches exist on the blind hole structure under a preset microscope magnification, thereby forming the sample to be tested.

8. The detection method according to claim 1, characterized in that: The combining of the grain diffraction image and the cross-sectional morphology image for analysis to obtain microstructure information characterizing the bottom of the blind hole includes: Acquiring information on grain size and grain growth status from the grain diffraction image; The cross-sectional morphology image characterizing the grain boundary, the grain size and the grain growth condition information are combined to obtain microstructure information characterizing the bottom of the blind hole.

9. An electronic device, characterized in that: The electronic device comprises: A memory for storing executable program codes; A processor is used to call and run the executable program code from the memory, so that the electronic device executes the packaging substrate detection method as described in any one of claims 1 to 8.

10. A computer-readable storage medium, characterized in that: The computer-readable storage medium stores a computer program, and when the computer program is executed by a processor, the method for detecting a packaging substrate according to any one of claims 1 to 8 is implemented.

Citation Information

Patent Citations

  • Method for processing metal-based hard coating transmission electron microscope in-situ mechanical sample by using focused ion beam

    CN111044543A

  • Preparation and characterization method of precious metal ultrafine wire EBSD test sample

    CN111289546A

  • Packaging substrate EBSD sample and preparation method thereof

    CN116297586A

  • FCBGA package substrate slice manufacturing method and blind hole test analysis method

    CN116718448A

  • Microscopic residual stress detection method

    CN117191580A

Cited By

  • Wire surface defect detection method and system based on image recognition model

    CN120510103A